A first approach for the micropropagation of the medicinal halophyte Polygonum maritimum L. and phenolic profile of acclimatized plants - Custódio, Luísa; Slusarczyk, Sylwester; Matkowski, Adam; Castañeda-Loaiza, Viana; Fernandes, Eliana; Pereira, Catarina; Rodrigues, Maria João (Frontiers in Plant Science, 2022)
Polygonum maritimum L. (sea knotgrass) belongs to a genus commonly used in folk medicine to treat inflammation-related disorders. In vitro pharmacological studies have confirmed these properties which were ascribed to bioactive flavonoids, such as myricetin and quercetin glycosides. Therefore, this study aimed at establishing a micropropagation procedure of sea knotgrass for obtaining standardized materials for its potential commercial cultivation. For that, a complete plant regeneration protocol was developed by improving shoot multiplication from nodal explants, rooting and acclimatization procedures, followed by the assessment of the phenolic profile of the in vitro-produced plants. The combination of 3 mg/L BA + 0.1 mg/L IAA induced the maximum shoot formation (10.3), which was significantly increased from the first to the second cycle (18.3). The best rooting capacity was observed on shoots derived from the control medium (100%), followed by 2 mg/L KIN (97%) and 3 mg/L BA + 0.1 mg/L IAA (90%), however the shoot number in the end of rooting phase was higher on shoots derived from 3 mg/L BA + 0.1 mg/L IAA (6.16). The plant growth regulators used in the multiplication phase influenced survival in the acclimatization process, and plants derived from the control medium had the highest survival percentage (63.1%). Acetone extracts made from aerial organs of micropropagated sea knotgrass showed a predominance of the flavonoid myricetin-3-O-rhamnoside (8.135 mg/g). Overall, the halophyte sea knotgrass was successfully micropropagated showing its potential as a medicinal crop for extraction of bioactive molecules.